PERAN GURU DALAM PEMBENTUKAN KARAKTERISTIK BELAJAR SISWA SEKOLAH DASAR - Niwi Sruti Handayani; Dini Rakhmawati (STKIP Subang, 2024)
As an educator, teachers play a significant role in the success of their students, not only in terms of academic knowledge but also in character development. At the elementary school level, teachers, in particular, bear a substantial responsibility not only to understand the characteristics of their students but also to assist in guiding the process of shaping their characters, particularly in the aspect of students' learning characters. The formation of these learning characters can be realized through the implementation of teaching strategies that align with facilitated instructional media, enabling students to actively participate in the teaching and learning process and ultimately achieve optimal learning outcomes. This research aims to explore the role of teachers in the process of shaping the learning character of elementary school students, along with the consequences if this role is not carried out effectively. The research employs a descriptive analysis method with data collection through literature review, using a qualitative research approach. From this study, it is revealed that teachers play an active role in the process of shaping students' learning character based on the teaching strategies they employ daily in the classroom. Teachers who use conventional and outdated teaching methods tend to create a dull learning environment, as elementary school students generally have a lively and playful learning character.